2009
DOI: 10.1021/ma802544q
|View full text |Cite
|
Sign up to set email alerts
|

Novel Self-Assembling Close-Packed Droplet Array at the Interface in Ternary Polymer Blends

Abstract: This paper reports, for the first time, on the self-assembly of polystyrene (PS) droplets into a perfectly segregated close-packed droplet array at a high-density polyethylene/polypropylene (HDPE/PP) interface during melt processing. Remarkably, even when highly concentrated at the interface, the PS remains in droplet form and does not coalesce into a uniform layer at the interface. This highly organized, Pickering-type emulsion microstructure is induced by the partial wetting of the HDPE/PP interface by the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
110
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(123 citation statements)
references
References 59 publications
11
110
0
2
Order By: Relevance
“…1a). Surface morphology of PS 50 /HDPE 50 blend was similar to the reports given in the literature where the diameters of circular PS patterns were between 2 and 20 m depending on the synthesis conditions [49,50]. In general, the polymer with lower Mw and SFE concentrates on the surface to minimize the interfacial tension between polymer/air interface and thus HDPE usually covers the surface of PS.…”
Section: Surface Characterization Of Micro-patterned Ps 50 /Hdpe 50 Psupporting
confidence: 82%
See 1 more Smart Citation
“…1a). Surface morphology of PS 50 /HDPE 50 blend was similar to the reports given in the literature where the diameters of circular PS patterns were between 2 and 20 m depending on the synthesis conditions [49,50]. In general, the polymer with lower Mw and SFE concentrates on the surface to minimize the interfacial tension between polymer/air interface and thus HDPE usually covers the surface of PS.…”
Section: Surface Characterization Of Micro-patterned Ps 50 /Hdpe 50 Psupporting
confidence: 82%
“…S2a) however, the adhesion of healthy leukocytes on this blend surface decreased approximately 2-fold when compared with HDPE surface and the positive selectivity ratio of L1210 cells/leukocytes increased from 1.8 to 3.5 on PS 50 /HDPE 50 (Fig. S2b).…”
Section: Surface Characterization Of Micro-patterned Ps 50 /Hdpe 50 Pmentioning
confidence: 90%
“…Nesta área, a mistura de polipropileno e poliestireno é uma das mais estudadas principalmente pelo baixo custo e relevância tecnológica destes materiais [1][2][3][4][5][6][7] . Por outro lado, a compreensão das relações processamentoestrutura-propriedade em misturas poliméricas de sistemas conhecido pode ser, e frequentemente é utilizado para explicar os comportamentos observados em sistemas poliméricos mais complexos.…”
Section: Introductionunclassified
“…Similar observations have also been reported on some ternary immiscible blends such as PP/PE/PS systems by Favis's group. [47][48][49] They found that the minor PS phase was dispersed as droplet form at the cocontinuous PP/PE phase interface because PS is incompatible with the two matrix polymers. As for the composite systems in this work, the appearance of such morphology is more or less confused because there is not the third component polymer or the formation of third component polymer incompatible with PC and PTT.…”
Section: Resultsmentioning
confidence: 99%